Conjunctival Flora Before and After Application of 5% Povidone-Iodine Solution - Vanzzini-Zago, Virginia; Villar-Kuri, Jorge; Alvarado, Víctor Flores; Marino, Alcántara Castro; Lilia, Pérez Balbuena Ana (IntechOpen, 2011)
None